2009
DOI: 10.2147/vhrm.s3223
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled iloprost for the control of pulmonary hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a life-threatening disease characterized by an elevated pulmonary arterial pressure and vascular resistance with a poor prognosis. Various pulmonary and extrapulmonary causes are now recognized to exist separately from the idiopathic form of pulmonary hypertension. An imbalance in the presence of vasoconstrictors and vasodilators plays an important role in the pathophysiology of the disease, one example being the lack of prostacyclin. Prostacyclin and its analogues are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 73 publications
0
20
0
1
Order By: Relevance
“…2 Iloprost is an inhaled prostacyclin drug that can act on the pulmonary blood vessels selectively and improve the hemodynamics of patients with PAH effectively; in addition, compared with traditional prostacyclin drugs, it has a longer halflife and can be administered by aerosol inhalation, avoiding the occurrence of infections, deep venous thrombosis, catheter displacement or pneumothorax resulting from previous iv medication. 3 These drugs can alleviate the symptoms in patients with PAH, and improve exercise capacity, hemodynamics and outcome. The clinical relevance of these effects, however, has been recently challenged, 4-6 mainly because of the limited amelioration of exercise capacity by medication, short duration and the small size of the individual studies, which have precluded any insight into the prognostic relevance of the treatments.…”
mentioning
confidence: 99%
“…2 Iloprost is an inhaled prostacyclin drug that can act on the pulmonary blood vessels selectively and improve the hemodynamics of patients with PAH effectively; in addition, compared with traditional prostacyclin drugs, it has a longer halflife and can be administered by aerosol inhalation, avoiding the occurrence of infections, deep venous thrombosis, catheter displacement or pneumothorax resulting from previous iv medication. 3 These drugs can alleviate the symptoms in patients with PAH, and improve exercise capacity, hemodynamics and outcome. The clinical relevance of these effects, however, has been recently challenged, 4-6 mainly because of the limited amelioration of exercise capacity by medication, short duration and the small size of the individual studies, which have precluded any insight into the prognostic relevance of the treatments.…”
mentioning
confidence: 99%
“…On the other hand, common adverse effects of inhaled iloprost include cough, headache, flushing, and jaw pain. In their study, Krug et al [16] showed serious side effects such as syncope, tachycardia, pneumonia, and dyspnea in 2 to 5% of the patients. In our study, no acute toxicities related to the inhalation of aerosolized iloprost and no systemic side effects were observed.…”
Section: Discussionmentioning
confidence: 94%
“…However, the effect of inhaled iloprost terminates between 6.4 to 9.5 minutes after inhalation, and it is necessary to use inhaled iloprost 6 to 12 times a day. The usual dosage is 2.5 μg per inhalation although it can be increased to 5 μg per inhalation [11]. PAH is characterized by the elevation of PAP as well as by early mortality.…”
Section: Discussionmentioning
confidence: 99%